MODEL BISNIS INKLUSIF UNTUK PEMBERDAYAAN PETANI KECIL DI KABUPATEN SAMBAS - Nugra Irianta Denashurya; Singgih Tiwut Atmojo; Irba Muhlas Sambodo (Jurnal Pertanian Agros, 2025)
Sambas Regency in West Kalimantan has significant agribusiness potential, yet smallholder farmers in the region continue to face various challenges such as limited access to markets, capital, and technology. This study aims to identify inclusive business models that have been implemented, evaluate their impact on the economic and social welfare of smallholder farmers, and examine the barriers faced in their implementation. A mixed-method approach was employed, collecting data through questionnaires, in-depth interviews, and field observations involving smallholder farmers, community leaders, and agribusiness actors. The findings show that inclusive business models involving partnerships between smallholder farmers and agribusiness companies have provided substantial benefits, including increased income, expanded market access, and capacity building through training and extension services. However, challenges such as bureaucratic complexity, inadequate infrastructure, and limited access to financing remain significant obstacles. The study concludes that inclusive business models hold great potential for empowering smallholder farmers, provided there is strong support from the government, the private sector, and financial institutions. Policy recommendations are proposed to strengthen the effectiveness of these models in promoting inclusive economic development in rural areas.